Strategi Dinas Pariwisata dalam Pengembangan Ekowisata Bukit Lawang Kecamatan Bahorok Kabupaten Langkat - Sembiring, Risky Rianda; Wulandari, Novita; Lubis, Khairunnisa (Jurnal Ilmiah Administrasi Publik dan Pemerintahan (JIAPP), 2025)
This study aims to find out the strategy of the Langkat Regency Tourism and Culture Office in the development of Bukit Lawang ecotourism. The main problems in this study are the decrease in the number of tourist visits, the lack of facilities and infrastructure in Bukit Lawang ecotourism, and low transparency in the allocation of government funds. In addition, the existence of a levy that is not clear in its use creates the impression of illegal levies, thereby reducing the interest of tourists. To analyze this problem, a SWOT analysis theory from Freddy Rangkuti was used. The data were collected through observation, interviews and documentation and analyzed qualitatively. This study concludes that the Tourism Office's Strategy in the Development of Bukit Lawang Ecotourism, Bahorok District, Langkat Regency is not optimal, still refers to the central strategy, although the Bukit Lawang tourist destination is known as the center of observation of Sumatrea orangutans and is included in the scope of Gunung Leuser National Park, there is no special strategy oriented to local wisdom as a special tourist attraction for tourists visiting Bukit Lawang.